Effects of Chinese cervical fixed-point rotation manipulation on heart rate variability in patients with sympathetic cervical spondylosis based on the theory of biomechanical equilibrium: a study protocol for a randomized controlled trial - Zeng, Xiayang; Zheng, Shengming; Xie, Yunxing; Ma, Hongyi; Zuo, Jinhong; Fan, Zhenyu; Qiu, Pengfei (Frontiers in Neurology, 2025)
BackgroundAs a complex cervical spondylosis with symptoms involving multiple systems and organs, SCS is easily misdiagnosed and underdiagnosed, and there is a lack of uniform efficacy assessment criteria for SCS, which causes great distress to patients and society. In this study, we will assesse the efficacy of cervical fixed-point rotational manipulation by combining HRV-related parameters and analyzing the correlation between the HRV and SCS.Methods/designIn this study, 90 participants will be randomly assigned at a 1:1:1 ratio into a test group (cervical fixed-point rotational manipulation manipulation group), a control group (sham manipulation group), or a Western medicine control group, with 30 participants in each group. All participants will be treated for a period of 4 weeks. The primary outcome indicators assessed is the HRV-related parameters, and the secondary outcome indicators are the NDI scale, NPQ scale, and HAMA scale. The assessment time points will be before and after treatment. The follow-up visits will be the first and sixth months after the end of treatment.DiscussionIn this study, SCS are treated with cervical fixed-point rotational manipulation based on the biomechanical balance theory, and HRV-related parameters are used for assessment to analyze the effect of cervical fixed-point rotational manipulation on heart rate variability in patients with SCS.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/, identifier ITMCTR2025000569.